Pengaruh Income, Debt, Gender Differences, Financial Literacy, dan Financial Attitude terhadap Financial Satisfaction - Ucik Siswoyo; Nadia Asandimitra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study examines the financial satisfaction among the employees in the District of Sidoarjo and analyses the relationship between income, debt, gender differences, financial literacy, and financial attitude. The object of this research is the employees in the District of Sidoarjo and data collection techniques using purposive sampling and snowball sampling. The total number of respondents obtained is 298 by distributing questionnaires online. This research is conclusive causality and uses Structural Equation Modeling (SEM) analysis technique in AMOS software version 24. This study showed that debt and financial attitude significantly affect financial satisfaction. In contrast, the variable income, gender differences, and financial literacy does not affect financial satisfaction. This study can be a valuable reference for various parties, especially employees, where you should always act and behave better in economic terms because the attitude towards finance plays a vital role in determining the success or failure of the financial behaviour of individuals. The high perspective of the individual financial can evaluate the heightened awareness in responsible for the expenditure of finances, so it will cause a positive impact on the behaviour of financial management to achieve the satisfaction of personal finance.